2021
DOI: 10.1038/s41598-021-99795-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of size and regional distribution of corpora amylacea in the hippocampal formation of obstructive sleep apnoea patients

Abstract: Corpora amylacea (CoA) are spherical aggregates of glucose polymers and proteins within the periventricular, perivascular and subpial regions of the cerebral cortex and the hippocampal cornu ammonis (CA) subfields. The present study quantified the distribution of CoA in autopsied hippocampi of patients with obstructive sleep apnoea (OSA) using ethanolamine-induced fluorescence. CoA were observed in 29 of 30 patients (96.7%). They were most abundant in periventricular regions (wall of lateral ventricle, alveus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Like PAS granules, CA formation is thought to be central to astrocytes, a prominent cell type in pial and subpial zones proximal to the glia limitans [ 16 , 59 ], where we note the accumulation of AT8 + structures in late-stage AD patients (Fig. 4 A and Table 4 ).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Like PAS granules, CA formation is thought to be central to astrocytes, a prominent cell type in pial and subpial zones proximal to the glia limitans [ 16 , 59 ], where we note the accumulation of AT8 + structures in late-stage AD patients (Fig. 4 A and Table 4 ).…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, CA accumulation or a related process, astrocytic clasmatodendrosis, may occur in brains from younger patients exposed to drug-induced stress [54,55]. Like PAS granules, CA formation is thought to be central to astrocytes, a prominent cell type in pial and subpial zones proximal to the glia limitans [16,59], where we note the accumulation of AT8 + structures in late-stage AD patients (Fig. 4A and Table 4).…”
Section: Discussionmentioning
confidence: 73%
“…Few studies have performed a quantitative analysis of CA across hippocampal regions. One study by Xu et al (2021) investigated CA distribution in sleep apnea patients and found CA were most abundant in periventricular regions (alveus, wall of lateral ventricle, fimbria) and undetectable in the CA2 region. Xu et al (2021) found few CA in the CA1 and CA3 regions.…”
Section: Discussionmentioning
confidence: 99%
“…One study by Xu et al (2021) investigated CA distribution in sleep apnea patients and found CA were most abundant in periventricular regions (alveus, wall of lateral ventricle, fimbria) and undetectable in the CA2 region. Xu et al (2021) found few CA in the CA1 and CA3 regions. In our study, CA3 exhibited a higher area occupied by CA than CA1.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor may be sleep disorders. In this sense, a high number of wasteosomes have also been described in the brains of patients with obstructive sleep apnea in a quantitative study performed by Xu et al ( 71 ). In that study, a large number of these structures were detected in almost all the specimens examined.…”
mentioning
confidence: 85%